2018
DOI: 10.1111/nyas.13667
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of visual symmetry and its role in mid‐ and high‐level visual processing

Abstract: Symmetry is an important and prominent feature of the visual world. It has been studied as a basis for image segmentation and perceptual organization, but it also plays a role in higher level processes, such as face and object perception. Over the past decade, there has been progress in the study of the neural mechanisms of symmetry perception in humans and other animals. There is extended activity in the ventral stream, including the lateral occipital complex (LOC) and VO1; this activity starts in V3 and it o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 147 publications
2
66
0
Order By: Relevance
“…Symmetry. One grouping principle for which evidence does exist, is symmetry, a higher-order regularity to which the human visual system is highly sensitive (for reviews, see Bertamini, Silvanto, Norcia, Makin, & Wagemans, 2018;Wagemans, 1997). In the study of Jacobsen and Höfel (2002), symmetry was found to be the most important factor in the aesthetic appreciation of graphic patterns.…”
Section: Simplicity Versus Ordermentioning
confidence: 99%
“…Symmetry. One grouping principle for which evidence does exist, is symmetry, a higher-order regularity to which the human visual system is highly sensitive (for reviews, see Bertamini, Silvanto, Norcia, Makin, & Wagemans, 2018;Wagemans, 1997). In the study of Jacobsen and Höfel (2002), symmetry was found to be the most important factor in the aesthetic appreciation of graphic patterns.…”
Section: Simplicity Versus Ordermentioning
confidence: 99%
“…The predictions of the holographic model have been tested empirically and have been shown to accurately relate to behavioural performance (Nucci & Wagemans, 2007) and neural activity (Makin et al, 2016). Makin et al (2016) conducted a large EEG/ERP study to investigate whether the W-metric predicts the amplitude of the symmetry-related component: the sustained posterior negativity (SPN; Bertamini, Silvanto, Norcia, Makin, & Wagemans, 2018;Höfel & Jacobsen, 2007;Jacobsen & Höfel, 2003;Jacobsen, Klein, & Löw, 2018;Makin, Wilton, Pecchinenda, & Bertamini, 2012;Martinovic, Jennings, Makin, Bertamini, & Angelescu, 2018;Wright, Mitchell, Dering, & Gheorghiu, 2018). Briefly, the SPN is a relative component given by the difference in amplitude between ERPs generated by symmetrical (regular) and asymmetrical (irregular) images with same local information.…”
Section: Introductionmentioning
confidence: 99%
“…Although this study has focused on face processing, a preference for bilateral symmetry is a more general property of the visual system (Bertamini et al, 2018;Keefe et al, 2018). The bias in neural processing is also evident in perceptual judgements showing that we are adept at discriminating small deviations in bilateral symmetry (Corballis and Beale, 1976;Rhodes et al, 2005) and find bilaterally symmetrical images more esthetically pleasing than nonsymmetric images (Jacobsen et al, 2006;Makin et al, 2012).…”
Section: Discussionmentioning
confidence: 94%